Efikasi Diri Dengan Kecemasan Akademik Pada Siswa Kelas XII Yang Hendak Mengikuti Ujian SNBT 2026 - Noveryn Setiawan; Sabrini Mentari Rezeki; Angel Chrismast Simarmata; Ananda Natalia Br Tarigan; Thessalonika Layasina Ginting; Rina Mirza (Jayapangus Press, 2026)
Academic examinations often trigger significant academic anxiety, especially among twelfth grade students who are preparing to take the SNBT examination. This condition is further intensified by the pressure of complex subject matter, intense competition, high expectations for academic achievement, and the implementation of TKA examinations. Low self-efficacy is considered one of the main internal factors that contribute to the increase in academic anxiety experienced by students. Therefore, the goal of this study is to analyze the relationship between self-efficacy and academic anxiety among twelfth grade students who are preparing to face their SNBT examinations. The research method used in this study was a quantitative correlational approach. The population of this study consisted of 424 twelfth grade students from SMA Negeri 5 Medan. The research sample included 191 students who were selected using a purposive sampling technique. Data were collected using Likert scale instruments consisting of an academic anxiety scale and a self-efficacy scale, both of which had been tested for their validity and reliability. Data analysis was conducted using the Pearson Product Moment Correlation technique with the assistance of IBM SPSS Statistics version 26 software. The results showed a correlation coefficient value of r=-0,441 with a significance level of 0,000 (p<0,05). These result indicate that there is a significant negative relationship between self-efficacy and academic anxiety. Based on the R Square value of 0,194, self-efficacy contributed 19,4% to academic anxiety, while the remaining 80,6% was influenced by the other variables outside this study. Overall, most students were categorized at a moderate level for both self-efficacy and academic anxiety.